Mobile apps for language learning - Godwin-Jones, Robert (Language learning & technology, 2011)
Portable audio-video and computing devices have long been a subject of interest for those interesting in language learning, and the smartphones and tablet computers of today feature enhanced capabilities that have dramatically increased the interest level in mobile learning, including among language educators. Godwin-Jones provides an overview of the potential of many of the apps (applications) available on these devices for use in language instruction and learning. Adapted from the source document